Postulation of a Union X⊂ℙr, r≥4, of a Given Zero-Dimensional Scheme and Several General Lines. (12th December 2013) - Ballico, E.
Abstract : We study the Hilbert function of the union X of a given zero-dimensional scheme Z ⊂ ℙ r, r ≥ 4, and t general lines of ℙ r, proving, for example, that if t ≫ deg ( Z ), then X has maximal rank.